Genetic parameters, correlation and path analysis for seed yield and morphological characters in niger [Guizotia abyssinica (L.f.) Cass.]: Genetic parameters, correlation and path analysis for seed yield and morphological characters in niger [Guizotia abyssinica (L.f.) Cass.] - D S SUTAR; S B GHUGE; S V PAWAR; P O BHUTADA (Journal of Oilseeds Research, 2020)
Twelve niger genotypes were tested in a randomized block design with three replications in kharif 2016-17 at AICRP on Safflower, Parbhani. The highest magnitude of GCV was obtained for number of capitula/plant (17.5) followed by plant height (14.9), number of productive branches (13.2) and seed yield (12.8) and low values of GCV estimated for plant stand (2.2), days to maturity (4.3), days to 50% flowering (4.6) and 1000 seed weight indicating the presence of lower genetic variability for these traits. Plant stand had significant positive correlation with number of productive branches/plant, number of capitula/plant, seed yield/plot, 1000-seed weight and seed yield (kg/ha) due to high positive direct and indirect effect.